Nerve transfer in children with acute flaccid myelitis for restoration of upper limb function (literature review) - O. E. Agranovich; I. A. Komolkin (Нервно-мышечные болезни)
The term “acute flaccid myelitis” is used to describe a condition characterized by acute flaccid paralysis of the limb, as well as damage to the motor neurons of the spinal cord. The absence of specific treatment, severe neurological deficit that persists in 75–95 % of patients in the long term indicates its severity.The aim of the work is to describe acute flaccid myelitis in children, modern methods of treatment, and estimate the effectiveness of nerve transfers for restoration of the upper limb function.The search for publications was carried out in the PubMed/MEDLINE, Google Scholar databases from 2003 to 2022, and data from the US Centers for Disease Control and Prevention (https://www.cdc.gov) were used. There were analyzed surgical treatments of 57 children with paresis of the upper extremities due to AFM (105 nerve transfers). Restoration of shoulder function (neurotization of n. axillaris, n. suprascapularis) was performed in 57 (54.3 %) patients, elbow flexion (neurotization of n. musculocutaneus) in 37 (35.2 %), elbow extension in 9 (8.5 %) (neurotization of the branch of n. radialis to m. triceps brachii), fingers flexion in 1 (1 %) (neurotization of the n. interosseus anterior branch), fingers extension in 1 (1 %) (neurotization of n. interosseus posterior).The review demonstrated the effectiveness of nerve transfers in children with paresis of the upper extremities due to acute flaccid myelitis who were operated up to 1 year from the onset of the disease.